Can Ophthalmologic Examination Predict Abducens Nerve Recovery After Endoscopic Skull Base Surgery?. (18th August 2020) - Whelan, Rachel L.; McDowell, Michael; Chou, Courtney; Medsinge, Anagha; Lee, Jennifer; Gardner, Paul A.; Snyderman, Carl H.; Stefko, S. Tonya; Wang, Eric W.
Abstract : Objectives: While abducens nerve palsy (ANP) is a known risk in the setting of some endoscopic endonasal skull base surgery (ESBS), frequency and prognosis of post‐operative palsy remain unknown. Our goals were to determine the frequency and prognosis of ANP after high‐risk ESBS, and identify factors associated with recovery. Methods: Retrospective case series of all patients with pathology at highest risk for abducens nerve injury (pituitary adenoma, chordoma, meningioma, chondrosarcoma, cholesterol granuloma) generated a list of patients with abducens nerve palsy after ESBS performed from 2011–2016. A validated ophthalmologic clinical grading scale measuring lateral rectus duction from 0 to −5 (full motion to inability to reach midline) was measured at multiple time points to assess recovery of ANP. Results: Of 655 patients who underwent ESBS with increased risk of abducens injury, 40 (6.1%) post‐operative palsies were identified and 39 patients with dedicated examination at multiple time points were included in subsequent analysis. Complete resolution was noted in 25 patients (64%) within 12 months. While 19 of 23 (83%) with a partial palsy had complete resolution, only six of 16 (38%) with a complete palsy resolved entirely ( P = .005; Fisher's exact test). All six patients with delayed onset of palsy resolved ( P = .070; Fisher's exact test). Meningioma and chordoma had higher rates of both temporary and permanent post‐operative ANP ( P  < .0001; Fisher's exact). Conclusions: The frequency of post‐operative ANP following ESBS is low, even in high‐risk tumors. While only a minority of complete abducens nerve palsies recover, patients with partial or delayed palsy post‐operatively are likely to recover function without intervention. Level of Evidence: IV Laryngoscope, 131:513–517, 2021